Running Retraining Technique and Neuromuscular Exercises in Runners with Patellofemoral Pain: A Scoping Review - Miguel Farraj; Thomas Guilhem; Joachim Van Cant; Alexandre Rambaud (International Journal of Sports Physical Therapy, 2025)
# Background